Fraudulent Financial Reporting: The Role of the Audit Committee in Mitigating Fraud Risk Factors - Suciati Rahmadani; Dewi Indriasih; Teguh Budi Raharjo (Universitas Pancasakti Tegal, 2026)
This study aims to analyze the influence of financial target, financial stability, total accrual, and ineffective monitoring on fraudulent financial reporting, as well as the role of the audit committee as a moderating variable. Secondary data was obtained from the financial statements of 53 companies in the subsector food and beverage listed on the IDX for the 2021–2025 period selected through purposive sampling. The analysis was conducted using descriptive statistics, tests of classical assumptions, multiple linear regression, Moderated Regression Analysis and hypothesis testing through SPSS 22. The study proves financial stability and total accrual has a positive effect on fraudulent financial reporting. The audit committee moderates the correlation of financial reporting between financial target and financial stability on fraudulent.